2013
DOI: 10.1152/ajpendo.00453.2012
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Fas activity rescues early onset of diabetes inc-KitWv/+mice

Abstract: Wv/ϩ mouse islets, suggesting that there is a critical balance between c-Kit and Fas activation in ␤-cells. In the present study, we investigated the interrelationship between c-Kit and Fas activation that mediates ␤-cell survival and function. We generated double mutant, c-Kit Wv/ϩ ;Fas lpr/lpr (Wv Ϫ/Ϫ ), mice to study the physiological and functional role of Fas with respect to ␤-cell function in c-Kit Wv/ϩ mice. Isolated islets from these mice and the INS-1 cell line were used. We observed that islets in c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 51 publications
(72 reference statements)
0
22
0
Order By: Relevance
“…Lack of functional FasR in c-Kit Wv/+ mice reduced the extent of beta cell apoptosis via downregulation of the caspase 8-mediated extrinsic apoptotic pathway, and enhanced FLICE-like inhibitor protein/nuclear factor κB pro-survival signalling [51]. These in vivo results were further supported by in vitro observations using INS-1 cells, whereby c-Kit activation negatively modulated both p53 and FasR in a PI3K-dependent manner.…”
Section: C-kit and Fas Receptor Interplay In Isletsmentioning
confidence: 64%
See 4 more Smart Citations
“…Lack of functional FasR in c-Kit Wv/+ mice reduced the extent of beta cell apoptosis via downregulation of the caspase 8-mediated extrinsic apoptotic pathway, and enhanced FLICE-like inhibitor protein/nuclear factor κB pro-survival signalling [51]. These in vivo results were further supported by in vitro observations using INS-1 cells, whereby c-Kit activation negatively modulated both p53 and FasR in a PI3K-dependent manner.…”
Section: C-kit and Fas Receptor Interplay In Isletsmentioning
confidence: 64%
“…Fas ligand binding and subsequent activation of FasR leads to programmed cell death in many systems via activation of the caspase 8-mediated downstream cell death machinery. We recently reported that deficient c-Kit signalling resulted in increased beta cell death in c-Kit Wv/+ mice, which was associated with upregulation of p53 levels and induction of FasR activity in c-Kit Wv/+ mouse islets [51] (Fig. 3).…”
Section: C-kit and Fas Receptor Interplay In Isletsmentioning
confidence: 90%
See 3 more Smart Citations